Food retailing, supermarkets and food security: Highlights from Latin America - Mehmet Arda (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The importance of supermarkets in the world food economy has increased radically since the early 1990s. They are now major sellers and buyers of food items not only in developed but also in developing countries. Urbanization and the liberalization of the services sector have been important facilitators of this process. Supermarkets have a significant impact on both producers and consumers. They provide relatively cheaper and better quality products, at least to some groups of urban consumers (the relatively better-off consumers in developing countries and the poor inner-city dwellers in more developed ones), thus contributing positively to their food security. Their global procurement networks, stringent quality requirements and financial muscle make this possible. The same factors, however, impact differently on producers. The suppliers who can abide by the quality standards, quantity requirements and the business practices of supermarkets, either alone or in association with others, benefit from these new retail channels. They also gain easier access to export markets. Smaller and poorer producers, who cannot meet these requirements, are left out, marginalized and often bought out by larger concerns, experiencing impoverishment and subsequent deterioration in their food security. Finally, employment in the traditional retail sector suffers with a non-negligible loss of employment. These global phenomena are examined and illustrated through examples from the Latin American region provided in the literature. Particular emphasis is put on fresh fruit and vegetables, products that have been studied most extensively, and milk. The case of potatoes illustrates the impact of the fast food industry, which is not much different from that of supermarkets. Some proposals are made to enable the more disadvantaged producers benefit from the opportunities presented by the advent of supermarkets.
Keywords: Q13; O13; O54; 330; food retailing; supermarkets; food security; value chains; Latin America; Lebensmitteleinzelhandel; SB-Lebensmittelgeschäft; Nahrungsmittelversorgung; Lateinamerika